2022
DOI: 10.1039/d1en01078f
|View full text |Cite
|
Sign up to set email alerts
|

Are nanomaterials leading to more efficient agriculture? Outputs from 2009 to 2022 research metadata analysis

Abstract: Agriculture is responsible for supplying food, feed, fibres, and an increasing fraction of fuel and raw chemicals for industry. Fulfilling such demands sustainably is one of the major challenges of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 107 publications
(156 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, better experimental design and standardized protocols are needed, because a large number of published studies lack adequate controls for comparison (e.g. with a commercial formulation or bulk materials), 23,63 making it difficult to assess the benefits of nano-enabled products. Furthermore, field testing is a critical step in ensuring the effectiveness of a nanoformulation.…”
Section: Associated Problems and The Ideal Nanodevicementioning
confidence: 99%
“…Nevertheless, better experimental design and standardized protocols are needed, because a large number of published studies lack adequate controls for comparison (e.g. with a commercial formulation or bulk materials), 23,63 making it difficult to assess the benefits of nano-enabled products. Furthermore, field testing is a critical step in ensuring the effectiveness of a nanoformulation.…”
Section: Associated Problems and The Ideal Nanodevicementioning
confidence: 99%
“…However, a study 80 evaluated the impact of GNMs at concentrations from 100 to 1000 mg kg −1 on earthworms, which is more representative of real application scenarios. A study 9 reported a median and mean dose of nanomaterial used in soil-based applications of 125 and 743 mg kg −1 for the timeline of 2009 to 2022, respectively. In a nematode based study, it was reported that a 130 day exposure to 10 g kg −1 of GNMs resulted in an increase of bacterivores and fungivores but a decrease in several nematode community parameters associated with diversity, species richness, and structure.…”
Section: Graphene Interaction With Agricultural Componentsmentioning
confidence: 99%
“…54 and 149), much higher in comparison of nanomaterial application of 0.4 to 1.7 t ha −1 (calculated based on the median value of 100 to 400 mg kg −1 soil for soil application of GNMs reported during year 2009 to 2022 (ref. 150) assuming a typical soil bulk density of 1.4 g cm −3 and soil depth of 30 cm). Thus, this low adsorbent (GNMs) to adsorbate (nutrient) ratio in the soil root zone, may limit the usefulness in employing GNMs for this purpose.…”
Section: Graphene Interaction With Agricultural Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, nanotechnological approaches have been introduced for the development of fertilizers [ 14 , 15 , 16 ]. Several studies have examined the potential absorption of nano- and micro-particles of sparingly soluble mineral compounds after foliar application, e.g., [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%